تأثير معاملة بذور الفول بالمبيدين Imidacloprid و Thiamethoxam في خفض نسبة الإصابة بفيروس التفاف أوراق الفول - قمري, صفاء; إسماعيل, عماد; الجلاد, رنا (Latakia University Journal -Biological Sciences Series, 2018)
هدف البحث إلى دراسة تأثير معاملة بذور الفول قبل الزراعة بمبيدي Thiamethoxam (تركيز 0.5 غ مادة فعالة/كغ بذور) وImidacloprid (تركيز 1.4غ مادة فعالة/كغ بذور) في خفض نسبة الإصابة بفيروس التفاف أوراق الفول (Bean leaf roll luteovirus) عن طريق مكافحة الناقل (حشرات المنّ). أظهرت النتائج انخفاض نسبة الإصابة بالفيروس عند وقوع العدوى بواسطة حشرات منْ البازلاء الأخضر في مرحلة البادرة (من 85% في معاملة الشاهد إلى 19% في معاملة المبيد Thiamethoxam)، وانخفض الفقد في الغلة بنسبة 60%. في حين لم تسجل إصابة بالفيروس في معاملة Imidacloprid في المرحلة نفسها، وبلغ خفض فقد الغلة 39% بالمقارنة مع الشاهد. بلغت الزيادة في إنتاج النباتات غير الملقحة بالفيروس والنامية من بذور معاملة بالمبيد Thiamethoxam 8% و 4% مقارنة مع الشاهد غير المعامل ومع النباتات المعاملة بذورها بالمبيد أميداكلوبريد، على التوالي. The aim of this experiment is to study the effect of per-sowing faba bean seeds treatment with insecticide thiamethoxam (0.5 g active ingredient/Kg seeds) on incidence reduction of Bean leaf roll luteovirus in comparison with the effect of insecticide Imidacloprid (1.4 g active ingredient /Kg seeds). Results showed reduction in the viral infection rate (from 85% in control treatment dawn to 19% in Thiamethoxam treatment) when inoculation using acyrthosiphon pisum. Harris was done in early stage of plant growth, and yield reduction was decreased by 60% compared to the control treatment. Viral infection was not recorded in imidacloprid treatment in this stage and its yield reduction was decreased by 39%. The yield of non inoculated plants grown from thiamethoxam treated seeds has increased by 8% and 4% in comparison with the yield of control grown from thiamethoxam non treated seeds and from imidacloprid treated seeds respectively.